Use of an improved radiation amplification factor to estimate the effect of total ozone changes on action spectrum weighted irradiances and an instrument response function - Herman, Jay (AGU, 2010)
Multiple scattering radiative transfer results are used to calculate action spectrum weighted irradiances and fractional irradiance changes in terms of a power law in ozone Ω, U(Ω/200)⁻ᴿᴬᶠ, where the new radiation amplification factor (RAF) is just a function of solar zenith angle. Including Rayleigh scattering caused small differences in the estimated 30 year changes in action spectrum-weighted irradiances compared to estimates that neglect multiple scattering. The radiative transfer results are applied to several action spectra and to an instrument response function corresponding to the Solar Light 501 meter. The effect of changing ozone on two plant damage action spectra are shown for plants with high sensitivity to UVB (280–315 nm) and those with lower sensitivity, showing that the probability for plant damage for the latter has increased since 1979, especially at middle to high latitudes in the Southern Hemisphere. Similarly, there has been an increase in rates of erythemal skin damage and pre-vitamin D₃ production corresponding to measured ozone decreases. An example conversion function is derived to obtain erythemal irradiances and the UV index from measurements with the Solar Light 501 instrument response function. An analytic expressions is given to convert changes in erythemal irradiances to changes in CIE vitamin-D action spectrum weighted irradiances.